Sistema web de gestión de los servicios de estadística y central de enfermería para el Hospital Básico 7 B.I Loja. - Capa Medina, Lenin Israel (2016)
This thesis research (PFC) titled, The Web Service Management System Statistics and Central Nursing For Basic Hospital 7 BI Loja, has been designed so that the health unit can use an integrated management system that provides timely information to statistical services, central nursing and various hospital medical offices throughout the hospital system. The methodology and development of this technology has been applied to the Windows XP Operating System. After multiple meetings with the client, the management system allows for the data entered to give a better understanding of the user which will serve as a foundation in which the appropriate management tool can be selected and implemented. The management system was developed using RUBY programming language and was assisted by the RUBY on Rails framework which is an open source technology. This provides the freedom to develop user-friendly websites that allows for the use of HTML, CSS, SASS, JQuery and CoffeeScript. These were also used for the preparation of the Frontend system. This technology also employed the use of GEMS as sorcery and found to be necessary for the preparation of reports and printed documents. Wicked_pdf tests were performed to ensure functionability, security and acceptance of load testing and system stress. During the development, the module statistic integrated with the software currently in use. This has allowed for the determination of patient processing registration which is diectly related to the module that doctors use in patient diagnosis and reporting. The management system compiles and segregates all relevant medical data for reporting to the Central Bureau of Nursing. Finally, the system has been integrated with the medical statistical units, central nursing, pharmacy and individual doctor offices which give immediate and user friendly solutions to health care professionals.